In-situ synthesis of TiO2/La2O2CO3/rGO composite under acidic/basic treatment with La3+/Ti3+ as mediators for boosting photocatalytic H2 evolution. (3rd September 2019) - Azam, Muhammad Usman; Tahir, Muhammad; Umer, Muhammad; Tahir, Beenish; Shehzad, Nasir; Siraj, Mohammad
Abstract: Graphene-bridged, carbonate-coordinated and lanthanum modified TiO2 nanocomposite (La/Ti 3+ /TiO2 /La2 O2 CO3 /rGO) was established using sol-gel assisted modified hydrothermal method followed by acidic/basic heat treatment. The synergistic effect of La/La2 O2 CO3 in rGO bridged Ti +3 /TiO2 nanocomposite was investigated for dynamic H2 production from ethylene glycerol-water mixture in a slurry phase continuous flow photoreactor system. La-TiO2 /rGO showed H2 evolution rate of 462 μmol/h which was about 1.24, 1.51 and 5.13 folds higher compared to La/TiO2, rGO/TiO2 and pure TiO2 samples, respectively. Furthermore, when La-TiO2 /rGO nanocomposite was treated under H2 /CO2 atmosphere, a great potential in photocatalytic H2 production with a rate of 583 μmol/h was obtained, which was ~1.02, 1.17 and 1.26 times higher than using H2, CO2 and N2 atmospheres, respectively. This significantly enhanced productivity was due to formation of La2 O2 CO3, increased absorptive properties of TiO2 and changes in elemental level like Ti 3+ state, which improves light absorption properties and producing more electrons with their hindered recombination rate by rGO. Specifically, existence of La2 O2 CO3 could facilitate the basicity of catalyst and contributes in the decomposition of ethylene glycol for H2 evolution. Next, apparent quantum yield of La-TiO2 /rGO calcined in CO2 /H2 composite was 1.3 folds higher than using La-TiO2 /rGO composite. Moreover, the stability comparison reveals that CO2 /H2 treated sample showed stability in cyclic runs due to better interactions of its components and formation of interface species like Ti 3+ and La2 O2 CO3 . Therefore, fabrication of composite under well-controlled atmospheric heat treatment could be promising to develop graphene supported metal oxides with their unique structures towards visible light enhanced photocatalytic H2 production applications. Graphical abstract: Image 1 Highlights: rGO/La doped TiO2 composite fabricated by treatment in CO2 /H2 atmosphere. La-co-catalyzed rGO-bridged TiO2 composite yielded H2 of 5.13 folds higher than TiO2. Catalyst heat treatment in CO2 /H2 atmosphere yielded 1.26 folds higher H2 than using N2 . Formation of Ti 3+, La2 O2 CO3 and increased conductivity of rGO improved efficiency of La-TiO2 /rGO. Catalyst treated in CO2 /H2 gave higher stability in cyclic runs than N2 atmosphere.